Optimization Student Learning Outcomes Through Hyflex Learning Based On Student Engagement - Parwati, Ni Nyoman; Suharta, I Gusti Putu; Sudatha, I Gde Wawan; Prameswara, Putu Buddhi; Halili, Siti Hajar (Journal of Applied Science, Engineering, Technology, and Education, 2025)
Student engagement is an important factor in determining learning outcomes, but in online learning in particular, many obstacles are still faced. On the other hand, studies on the implementation of effective online learning are still limited. This study aims to: 1) produce an empirical mapping of the implementation of online learning based on student engagement and its impact on their learning outcomes, 2) describe the characteristics of HyFlex learning based on student engagement and 3) describe respondents' opinions about student engagement in HyFlex learning. The research instruments used were observation sheets, document recording sheets, questionnaires and interview guides. Data were analyzed using a meta-analysis method by calculating the effect size of selected articles, complemented by qualitative descriptive analysis. The results of the study are: 1) student engagement is significantly positively correlated with student learning outcomes, indicating a strong influence in the high category. 2) identification of valid HyFlex learning characteristics based on student engagement to optimize their learning outcomes, and 3) respondents' opinions about student engagement in HyFlex learning are very positive, with an average of 73% good responses in both synchronous and asynchronous modes. Future researchers can further develop and apply the HyFlex Model in different environments.